Students' Socio-scientific Reasoning to Measure Decision-Making Ability Related to Sustainable Energy Issues - Rifqi Anjar Mustika; Wirawan Fadly; Martinez David (Yayasan Keluarga Guru Mandiri, 2025)
Along with the development of the era and technology and the increasing human population, the need for energy use is increasing. This study aims to measure students' reasoning and decision-making abilities related to socio-scientific problems. This study uses quantitative research with a cross-sectional survey research design. The research sample was determined by purposive sampling, and 26 samples were collected from class VII B at SMPN 1 Sambit Ponorogo. Measurements in this study were carried out through 2 tests: the first was a multiple-choice test, and the second was a descriptive test. The results of this study show that the Cronbach Alpha value in the form of interaction between person and item items as a whole, worth 0.72, is a